LOOKING FOR THE “ANTIBODIES” AGAINST GENDER DISCRIMINATION IN THE AI ACT (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The technological evolution, increasingly developing in a globalized world with the creation of «intelligent» systems, inevitably produces results that often escape human control. Among these are the often-unintentional distorting effects of algorithms on women. With the AI Act, the EU aims to limit such distortions through rigorous regulation to protect fundamental rights. This paper explores the different tools, implicit and explicit, offered by the new regulations to tackle gender discrimination.
Keywords: AI Act; impact assessment; fundamental rights; gender discrimination; vulnerability